Pembatalan Perkawinan karena Istri Mengandung Anak yang Bukan dari Suaminya Menurut Hukum Islam Studi Putusan Nomor 1478/Pdt.G/2022/PA.Kng - Nisfyandini, Agisna Cahya; Murniati, Murniati; Madinah, Dina (Sekolah Tinggi Ilmu Syariah Husnul Khotimah, 2025)
Marriage annulment, or fasakh, is the termination or dissolution of a marital relationship between husband and wife caused by the non-fulfillment of the pillars and conditions of marriage, or the discovery of certain circumstances after the marriage has taken place which renders the marriage invalid. This study aims to examine the judge’s decision and to analyze the perspective of Islamic law regarding the annulment of marriage due to the wife being pregnant with a child not from her husband (case study of Decision Number 1478/Pdt.G/2022/PA.Kng). The research method employed is a qualitative approach with the type of field research. Data collection techniques used in this study include interviews and documentation. The interview was conducted with the Religious Court Judge of Kuningan who handled the annulment case in Decision Number 1478/Pdt.G/2022/PA.Kng. The findings of this research show, first, that the petition was granted by the judge and the marriage between the petitioner and the respondent was annulled; therefore, the marriage certificate issued by the Office of Religious Affairs no longer holds legal validity, and the judge imposed court costs on the petitioner. Second, the judge’s decision to annul the marriage is in accordance with the provisions of Islamic law, as it was based on considerations of fraud and misunderstanding within the marriage, which are among the factors that justify fasakh or marriage annulment. Moreover, the marriage of a pregnant woman to a man other than the one who impregnated her is not permissible, as only the man responsible for the pregnancy has the right to marry her. This is in line with Article 53 of the Compilation of Islamic Law and the Qur’an, Surah An-Nur verse 3. As a consequence of the annulment decision, the marriage certificate registered at the Office of Religious Affairs is deemed legally invalid, as the marital relationship has been dissolved, thereby restoring both parties to their original status as unmarried.